Meat and bone meal stimulates microbial diversity and suppresses plant pathogens in asparagus straw composting - Liu, Xinxin; Li, Xiaoxiao; Hua, Yinfeng; Sinkkonen, Aki; Romantschuk, Martin; Lv, Yanfang; Wu, Qian; Hui, Nan (Frontiers in Microbiology, 2022)
Meat and bone meal (MBM), as slaughterhouse waste, is a potential biostimulating agent, but its efficiency and reliability in composting is largely unknown. To access the MBM application on the composting process of asparagus straw rice, we followed composting process for 60 days in 220L composters and another 180 days in 20L buckets in treatments applied with MBM or urea. The microbial succession was investigated by high-throughput sequencing. Compare to urea treatments, MBM addition stabilized pH and extended thermophilic phase for 7 days. Germination index of MBM treatments was 24.76% higher than urea treatments. MBM also promoted higher microbial diversity and shifted community compositions. Organic matter and pH were the most significant factors that influences on bacterial and fungal community structure. At the genus level, MBM enriched relative abundances of organic matter degrading bacteria (Alterococcus) and lignocellulose degrading fungi (Trichoderma), as well as lignocellulolytic enzyme activities. Notably, MBM addition decreased sum abundances of plant pathogenic fungi of Phaeoacremonium, Acremonium, and Geosmithia from 17.27% to 0.11%. This study demonstrated the potential of MBM as an effective additive in asparagus straw composting, thus providing insights into the development of new industrial aerobic fermentation.